Udenafil for the treatment of erectile dysfunction - Cho MC; Paick JS (Dove Medical Press, 2014)
Min Chul Cho,1 Jae-Seung Paick21Department of Urology, Dongguk University College of Medicine, Goyang, Korea; 2Department of Urology, Seoul National University College of Medicine, Seoul, KoreaAbstract: Erectile dysfunction (ED) is often perceived by both patients and sexual partners as a serious problem that can jeopardize quality of life, psychosocial or emotional well-being, and the partnership in the long term. Since their introduction, oral phosphodiesterase type 5 inhibitors (PDE5Is) have been found to be highly effective and well tolerated, and are available as the first-line therapy for the treatment of ED. Udenafil is one of the selective PDE5Is made available in recent years for the treatment of ED. Udenafil has clinical properties of both relatively rapid onset and long duration of action due to its pharmacokinetic profile, thereby providing an additional treatment option for ED men to better suit individual needs. There is positive evidence that udenafil is effective and well tolerated in the treatment of ED of a broad spectrum of etiologies or severity. Udenafil is as effective in the treatment of diabetes mellitus-associated ED as other PDE5Is. Due to the clinical property of relatively long duration of action, udenafil may be another option in daily dosing treatment for ED, as suggested by its favorable efficacy and safety profile. Most adverse effects reported from clinical trials are mild or moderate in severity, without any serious adverse event, with headache and flushing being the most common. Also, the concomitant use of anti-hypertensive drugs or alpha-1-blockers does not significantly affect the efficacy and safety profile of udenafil. However, additional studies with larger cohorts including prospective, multicenter, comparative studies with patients of different ethnicities are needed to further validate the favorable findings of udenafil in the treatment of ED.Keywords: udenafil, erectile dysfunction, therapy